Wisata Super Premium Labuan Bajo: Mengkaji Peran Langsung dan Tidak Langsung Terhadap Visiting Intention Ditinjau dari Destination Image dan Tourist Expectation - Lusy Asa Akhrani; Muhammad Azhar (Personifikasi: Jurnal Ilmu Psikologi, 2021)
The Indonesian government was planning a super premium tour of Labuan Bajo to be realized in 2020. Still, the change in this type of tourism resulted in various changes in travel behaviour. This study aims to examine the direct and indirect role of visiting intentions to Labuan Bajo through the destination image and tourist expectation. This research involved 141 tourists who have been and who have a desire to visit Labuan Bajo. Researchers used three scales of analysis, namely the scale of destination image, traveller expectations and visiting intentions. The analysis of this study uses multiple linear regression. The results showed a direct or indirect role of the destination image toward visiting intentions. There are two direct roles obtained, the first direct role from the destination image to the visiting intention and the other direct role from tourist's expectation towards visiting intentions. In contrast, the indirect role of the destination image generated through the expectation of a traveller toward visiting intention. Other results show that there is a simultaneous role between destination image and tourist expectations of the intention to visit Labuan Bajo.